2021
DOI: 10.1097/cad.0000000000001186
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of anlotinib as first-line treatment for elderly patients with advanced lung adenocarcinoma without driver gene mutations

Abstract: This retrospective study was conducted to explore the effects of anlotinib as first-line treatment for patients with advanced lung adenocarcinoma. We retrospectively reviewed medical records of 60 patients with advanced lung adenocarcinoma, admitted to the Fuzhou Pulmonary Hospital between August 2018 and December 2019. We calculated and recorded the objective remission rate (ORR), disease control rate (DCR), adverse reactions, quality of life assessment, progression-free survival (PFS) and overall survival (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(24 reference statements)
1
4
1
Order By: Relevance
“…The ORR and DCR were 21.6 and 100%, respectively; these rates were higher than those of the patients in the 0303 clinical trial study (9.2 and 81%, respectively) (Han et al, 2018). The DCR (100%) in the present study was much higher than that of anlotinib monotherapy (67.5%) and pemetrexed monochemotherapy (65.5%) in elderly advanced NSCLC patients (Zhu et al, 2021). In addition, the median PFS was 8.4 months, which was longer than that of DEB-BACE treatment (7.4 months) (Liu et al, 2021) and that of anlotinib monotherapy in advanced NSCLC patients (5 months) (Wu et al, 2019).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The ORR and DCR were 21.6 and 100%, respectively; these rates were higher than those of the patients in the 0303 clinical trial study (9.2 and 81%, respectively) (Han et al, 2018). The DCR (100%) in the present study was much higher than that of anlotinib monotherapy (67.5%) and pemetrexed monochemotherapy (65.5%) in elderly advanced NSCLC patients (Zhu et al, 2021). In addition, the median PFS was 8.4 months, which was longer than that of DEB-BACE treatment (7.4 months) (Liu et al, 2021) and that of anlotinib monotherapy in advanced NSCLC patients (5 months) (Wu et al, 2019).…”
Section: Discussioncontrasting
confidence: 63%
“…Anlotinib was recommended as the thirdline or further-line treatment for NSCLC and showed a significant effect on prolonged survival and tolerable toxicity. Many scholars recommend anlotinib as the first-or second-line treatment, not only the third-or further-line treatment regimen (Zhu et al, 2021). Zhong et al (2020) confirmed that PFS was longer when anlotinib was used in first-/second-line treatment than in thirdor further-line treatment of advanced NSCLC.…”
Section: Discussionmentioning
confidence: 93%
“…There have also been more studies of anlotinib as a first-line treatment in the last 2 years, and most of these studies have adopted the combination therapy model. The latest clinical analysis of first-line therapy in elderly patients with advanced lung adenocarcinoma without driver gene mutations showed similar median PFS (3.0 m vs. 2.8 m) and OS (7.0 m vs. 7.0 m) in the anlotinib group and the chemotherapy group (P > 0.05), and there was no significant difference in ORR (17.5 vs. 15%) or DCR (67.5 vs. 65.5%) between both treatment groups (23). The other studies have shown that, for driver gene-negative NSCLC patients, the median PFS in the anlotinib combined with chemotherapy group was 1.54 months longer than that in the chemotherapy group (9.38 months vs. 7.84 months, P < 0.05), and the median OS in the anlotinib combined with chemotherapy group was longer as well (11.52 months vs. 10.46 months), but the difference was not statistically significant (P > 0.05) (24).…”
Section: Discussionmentioning
confidence: 88%
“…A study on inoperable NSCLC patients indicated that the median PFS of sequential chemoradiotherapy patients was 10.8 months, but grade 3 acute esophagitis occurred in four of 78 patients (5%) ( 25 ). As shown in Table 2 ( 18 , 23 , 26 ), anlotinib is promising for the first-line treatment for NSCLC with its median PFS range of 3.0 to 15.0 months.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, National Medical Products Administration (NMPA) officially approved anlotinib monotherapy based on ALTER0303 in patients with advanced NSCLC progressing after second-line or further treatment, providing a new choice for Chinese patients. Recently, some retrospective studies demonstrated the effectiveness and safety of anlotinib in Chinese elderly patients with NSCLC as a first-line therapy setting ( 20 , 21 ), suggesting that anlotinib could be used as a first-line treatment in Chinese elderly NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%